2008
DOI: 10.1093/humrep/den332
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the optimal day for oocyte retrieval based on the diameter of the dominant follicle in hCG-primed in vitro maturation cycles

Abstract: Our results suggest that oocyte collection in IVM cycles should be performed when the DF is 14 mm diameter or less. Sibling immature oocytes may be affected detrimentally if a DF >14 mm is present at oocyte collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 22 publications
3
76
0
3
Order By: Relevance
“…In addition, they also did not mention whether they used the same criteria for triggering hCG as their previous study or not. We have previously reported that there were no differences in the rates of clinical pregnancy and implantation between the IVM cycles where embryos were transferred with and without embryos produced from in vivo matured oocytes when hCG priming was administered when the DF reached 10-12 mm, even though the study groups were for women who had polycystic ovaries [18]. Our present data is also consistent with that of Paulson et al [19], who reported that all pregnancies occurred in the cycles in which one of the embryos was derived from the DF (17 %, 11/66) in unstimulated IVF cycles of women with regular cycles and all of the implantations were singleton.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, they also did not mention whether they used the same criteria for triggering hCG as their previous study or not. We have previously reported that there were no differences in the rates of clinical pregnancy and implantation between the IVM cycles where embryos were transferred with and without embryos produced from in vivo matured oocytes when hCG priming was administered when the DF reached 10-12 mm, even though the study groups were for women who had polycystic ovaries [18]. Our present data is also consistent with that of Paulson et al [19], who reported that all pregnancies occurred in the cycles in which one of the embryos was derived from the DF (17 %, 11/66) in unstimulated IVF cycles of women with regular cycles and all of the implantations were singleton.…”
Section: Discussionmentioning
confidence: 93%
“…Ovarian tissue cryopreservation (OTC) is an alternative protocol that has attracted interest due to the fact that the only precondition for its application is the presence of ovaries, while variables such as age [9], menstrual cycle phase [12,25] and subjacent disease do not have a bearing on whether or not it can be performed. In addition, the tissue reimplantation that follows depends purely on the absence of malignant cells [2,13,20,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Retrieval of immature oocytes from unstimulated ovaries followed by IVM is an effective treatment option for many infertile women [4,5,11,25] and cancer sufferers. In oncologic patients, oocytes can be retrieved by means of standard oocyte aspiration [12,15] or in association with OTC [9,10,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited number of oocytes obtained by aspiration (3.3 in average), clinical pregnancy rate of 36.4% was achieved, which is between the 17 to 41% rate that is reported for this technique. Eventhough there are reports that claim an advantage in the administration of hCG before obtaining the oocytes (Son et al, 2008a, 2008b, Tan & Child, 2002, Chian, 2004 it's being also manifested that hCG interrupts comunication between follicular cells and the oocyte; this is an important event to the adquisition of a good embryonary potential development (Albertini et al, 2001). In our IVM protocol, we do not use hCG in vivo.…”
Section: Discussionmentioning
confidence: 99%